PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS NASABAH TABUNGAN PADA BANK NAGARI CABANG AUR KUNING KOTA BUKITTINGGI - Winda Octaviani; Yulhendri Yulhendri; Rose Rahmidani (Jurnal Ecogen, 2018)
This study aims to know and prove how much influence Customer Relationship Management (CRM) on customer loyalty at Bank Nagari Branch Aur Kuning in Bukittinggi City.This type of research is causative. The population in this study were customers of Bank Nagari Branch Aur Kuning. The samples were taken using Slovin formula with 100 respondents. This sampling technique is based on accidental sampling method. The type of data used in this study is primary data and secondary data. Data analysis technique used multiple regression analysis technique using SPSS version 15.00. The results of this study indicate that: 1) Trust has a positive significant effect on customer loyalty, 2) Commitment has a negative and not significant impact on customer loyalty, 3) Communication has a positive significant effect on customer loyalty. Keywords: Trust, Commitment, Communication and Loyalty